MicroRNA/microRNA* complementarity is important for the regulation pattern of NFYA5 by miR169 under dehydration shock in Arabidopsis. (29th April 2017) - Du, Qingguo; Zhao, Meng; Gao, Wei; Sun, Suzhen; Li, Wen‐Xue
Summary: MicroRNAs regulate gene expression at the mRNA and translational levels. Although our previous research showed that expression of miR169 and one of its targets, NFYA5, is down‐ and up‐regulated by drought stress, respectively, the current study shows that expression of both miR169 and NFYA5 are induced by dehydration shock. Unlike overexpression of MIR169a/b, overexpression of MIR169i/l did not decrease NFYA5 transcripts but increased NFYA5 protein levels. NFYA5 protein abundance also increased in mir169a knock‐out mutants and 35S::MIR169l   mir169a double mutants. When bulge #11 and bulge #16 in the miR169/miR169* duplex were mutated, both NFYA5 transcripts and the corresponding protein levels were lower in 35S::MIR169l*‐mut transgenic plants than in wild‐type (WT) plants, and the 35S::MIR169l*‐mut transgenic plants were as sensitive to drought stress as the 35S::MIR169a plants. The mRNA and protein levels of NFYA5 did not differ substantially between WT and 35S::MIR169a*‐mut transgenic plants when the two bulges were introduced in the miR169a/miR169a* duplex. Both bulge #11 and bulge #16 in the miR169/miR169* duplex were essential for different regulation patterns of NFYA5 by miR169a and miR169l. These results increase the understanding of regulatory specialization in one MIR family, and also increase our understanding of the importance of microRNA/microRNA* secondary structure. Significance Statement: We report that unlike miR169a, which mainly regulates NFYA5 expression at the mRNA level, miR169l mainly affects NFYA5 expression at the translational level. Most importantly, we identify microRNA/microRNA* complementarity as the determinant causing differences in the regulation pattern of NFYA5 by miR169a and miR169l. Our results increase the understanding of regulatory specialization in one MIR family and also increase our understanding of the importance of microRNA/microRNA* secondary structure.